Analysis Of Antituberculosis Drug Program Utilization In Tuberculosis Patients At The Outpatient Installation Of Pindad General Hospital, Bandung - Ulpa; Rida Emelia (International Journal of Health Sciences, 2026)
Tuberculosis (TB) remains an infectious disease that requires long-term and standardized treatment to achieve therapeutic success. Appropriate use of antituberculosis drugs and regular monitoring are important components of the TB control program. This study aimed to describe the characteristics of TB patients, treatment phases, antituberculosis drug regimens, and additional medications administered to patients at the outpatient installation of Pindad General Hospital, Bandung. This study used a descriptive observational design with a retrospective approach. Data were obtained from secondary data consisting of TB patient prescriptions and treatment records recorded in the Tuberculosis Information System (SITB) during March–April 2026. The study population consisted of 30 TB patients, and total sampling was used. Data were analyzed descriptively using frequencies and percentages. Of the 30 patients, 19 (63.3%) were male and 11 (36.7%) were female. The largest age group was 0–10 years, comprising 14 patients (46.7%). Based on treatment phase, 10 patients (33.3%) were in the initial intensive phase and 20 patients (66.7%) were in the continuation phase. Antituberculosis therapy was administered using Fixed-Dose Combination (FDC) regimens, including 4FDC for adults and 3FDC for children during the intensive phase, and 2FDC during the continuation phase. Additional medications included Vitamin B6, multivitamins, Curcuma preparations, and other supportive medications. All patients (100%) were still undergoing treatment, so treatment outcomes had not been completed. TB patients at Pindad General Hospital were predominantly male and aged 0–10 years. Most patients were in the continuation phase and received FDC antituberculosis therapy. Regular prescription screening and treatment monitoring are needed to support the appropriate implementation of the TB treatment program..